The Optical-Coenaesthetic Disproportion Hypothesis of Feeding and Eating Disorders in the Light of Neuroscience - Stanghellini, Giovanni; Ballerini, Massimo; Mancini, Milena (Frontiers in Psychiatry, 2019)
This paper builds on and extends the ‘optical-coenaesthetic disproportion’ (OCDisp) hypothesis of feeding and eating disorders (FED) matching data obtained through clinical research with lab evidence from neuroscience and neuropsychological studies. The OCDisp hypothesis, developed through the assessment in clinical setting of bodily experience using the IDentity and EAting (IDEA) disorder questionnaire, argues that in persons with FED the internal perception of one’s embodied self (i.e. coenaesthesia) is troubled and, as a compensation to it, these persons experience their own body as an object that is looked at by others. To FED persons, their body is principally given to them as an object ‘to be seen’. The other’s look serves as an optical prosthesis to cope with hypo- and dis-coenaesthesia and as a device through which persons with FED can define themselves and attenuate the anxiety produced by the conflicts between being-oneself and being-for-others. After describing the OCDisp hypothesis, we will gather evidence supporting it with neuroscience studies on FED. Our focus will be on data pointing to dampened multisensory integration of interoceptive and esteroceptive signals, demonstrating a predominance of the visual afferents toward signals arising within the body. In the final part of the paper we will show consistencies but also draw distinctions between our clinical hypothesis and neuroscience-based data and hypotheses and draft a potential agenda for translational research inspired by these.